The Influence of Reputation of Public Accounting Firms on the Integrity of Financial Statements with Corporate Governance as the Moderating Variable - Nera Marinda Machdar; Dade Nurdiniah (Bina Nusantara University, 2018)
This research aimed to determine the effect of the reputation of the public accounting firm on the integrity of financial statements by including leverage and firm size as the control variables. This research also investigated the effects of corporate governance moderation that was proxied by the independent commissioner, institutional ownership, and audit committee in strengthening or weakening the reputation of the public accounting firms on the integrity of the financial statements. The population was manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013-2015. The sample utilized the purposive sampling method and resulted in 34 manufacturing firms, so the total observations were 102 firms in all observed years. This research performed statistical data processing with EVIEWS 8. There are two main findings of this research. First, the reputation of public accounting firm affects the integrity of the financial statement. Second, corporate governance that utilizes the independent commissioners and institutional ownership strengthen the effect of the reputation of the public accounting firm on the integrity of the financial statement. However, corporate governance using audit committee weakens the reputation of the public accounting firm on the integrity of financial statements.